Comparing regional models of congenital bleeding disorders: preliminary steps in the Italian context - Nuti, Sabina (BMC Res Notes, 2017)
BACKGROUND: Among these diseases, congenital bleeding disorders (CBD) represent a significant societal burden in terms of high morbidity costs and health outcomes. In Italy, the organization and provision of health care is a regional responsibility and regions must assure equity and quality to all their residents. This is also true for CBD care which is provided by 54 multidisciplinary Hemophilia Treatment Centers (HTCs) distributed among the regions. With the present study, we intend to stimulate a debate on the effect that the decentralization process have in the delivery of services to CBD patients across Italy. METHODS: The available comparable measures of caseloads per center and interregional patient mobility, as proxies of quality and responsiveness of the regional network of HTCs, were first analyzed for the using data from the Italian Hemophilia Centers Association for the year 2012. RESULTS: Nine thousand one hundred and thirty four Italian residents with CBD received care in at least one of the Italian HTC in 2012. Preliminary findings suggested room for improvement in health care delivery for CBD patients. In 2012, 16 HTCs out of 51 (31.4%) treated a number of patients under the minimum requirement for treatment center accreditation (10 severe patients). Moreover, data on interregional patient mobility highlighted differences in the ability of each region to retain its own residents or to attract residents from other regions. CONCLUSIONS: Preliminary study results showed significant disparities among regions in terms of volumes and mobility of residents with CBDs that cannot be completely explained by the different geographical characteristics. Therefore, the central government should consider taking concrete measures to bridge the gap between regions to assure access to quality care for all individuals with CBD independently from where they live and therefore to move toward a more integrated and homogeneous national network of care centers. Typology of disease, patients’ needs, and cost for outcomes, should have high priority on the political agenda. For CBD patients, even in a federal healthcare system, the national government should have the global responsibility to guaranteeing uniform levels of quality care over the country and overcome local institutions when necessary.